Two new species of Triozocera Pierce, 1909 (Insecta: Strepsiptera: Corioxenidae) from the Caribbean Islands - Cook, Jerry L. (Zootaxa, 2022)
Triozocera albocciput and Triozocera macrognathus are described from the Caribbean Islands. These new species constitute the only known Triozocera from this region. Triozocera albocciput occurs in the Dominican Republic, Puerto Rico, and Cuba. The specimen from Cuba had previously been misidentified in the literature, as Triozocera mexicana and later Triozocera texana. The new species described here, as well as all other valid species in North America, are known only from male specimens.